2007
DOI: 10.3923/pjbs.2007.710.717
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Physico Chemical Properties of Water of Mouri River, Khulna, Bangladesh

Abstract: Water sample were collected from six different point of the Mouri River Khulna, Bangladesh with a regular intervals in the months of January-March 2002 for the analyzing different physicochemical parameters of the water. Total 22 different physicochemical parameters were investigated. Correlation and the t value among the parameters were also determined. In the present investigation the minimum and maximum value of water temperature, Transparency, Turbidity, TSS, TDS, Electric Conductivity, water pH, dissolve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 7 publications
6
22
3
1
Order By: Relevance
“…Dissolved oxygen concentration in St.1 , St.3, St.4, St.5 and St.6 was above 5 mg/l which indicate a better condition for aquatic organisms. In the Buriganga River DO concentration was found 2-3 mg/l that indicates high rate of pollution (Moniruzzaman et al, 2009 Roy (1955) and (7.3-8.3) in Mouri river by Khan et al (2007) also showed a buffer condition which are in agreement with the finding of the present study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Dissolved oxygen concentration in St.1 , St.3, St.4, St.5 and St.6 was above 5 mg/l which indicate a better condition for aquatic organisms. In the Buriganga River DO concentration was found 2-3 mg/l that indicates high rate of pollution (Moniruzzaman et al, 2009 Roy (1955) and (7.3-8.3) in Mouri river by Khan et al (2007) also showed a buffer condition which are in agreement with the finding of the present study.…”
Section: Discussionsupporting
confidence: 83%
“…The variations were further aggravated by heavy precipitation during the monsoon. The range of water temperature of Dhepa river is not similar to that obtained for river Talar 10.10-29.7°C (Alavi and Jafari, 2010) and for river Mouri 22.1-23.5°C (Khan et al, 2007). These might be different geological position of this river.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The sample selection site should be representative of the water body being investigated. Sampling sites selection of Mouri river [64] did not explain well enough by providing information whereas the sampling sites selection in Buriganga river [20] industrial zone of Dhaka [97] were explained along with sufficient information. The study period for environmental research conveys a significant essence to evaluate the pollution status of water body.…”
Section: Handicap In Sampling and Analysismentioning
confidence: 87%
“…In ground water of that region DO is negatively correlated with pH (r= -0.04) [68] which indicates that the correlation is completely depends on surrounding environment and sources. A correlation study of the Mouri river visualized that temperature, pH, hardness, TA, DO, free CO2 and sulphate were in positive correlation [64].…”
Section: Pearson's Correlationmentioning
confidence: 99%